Gathering Evidence of Learning in Library Curriculum Center Spaces with Web GIS - Stoddart, Rick; Godfrey, Bruce (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This article reports on a pilot research project that gathered usage statistics in specifically designated library learning spaces using a Web-based Geographic Information System (GIS). These learning spaces were then mapped to expected learning activities that would occur in these areas based on its intention or design. In this way, the library could begin to associate the usage of a space with different types of learning. The researchers then mapped these learning activities to campus learning outcomes to create learning impact statements.Methods – The researchers used observation data gathered with a Web GIS tool to examine space usage within the library’s curriculum center.Results – The pilot study found that student usage of the curriculum center was mainly associated with two campus learning outcomes: (1) Communicate and (2) Learning and Integrate. The evidence also indicated possible design improvements that may make the curriculum centers spaces more functional for students.Conclusions – The Web GIS tool proved to be a useful tool to gather evidence of student space usage within the library environment. The mapping of individual spaces to learning activities further enhanced the usefulness in interpreting how students are using library spaces. Leveraging the space usage data within learning outcomes statements created another means for the library to communicate its learning impact with campus stakeholders.